Pengembangan Perangkat Pembelajaran Matematika Model Kooperatif Dengan Pendekatan Kombinasi Experiences, Language, Pictorial, Symbol, Application (ELPSA) Dan Saintifik - Muhammad Assaibin; Hamzah Upu; Muhammad Darwis (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2019)
The research was Development Research with limited test which aimed to develop Mathematics learning devices with Cooperative Model with The Combination Of Experiences, Language, Pictorial, Symbol, Application (ELPSA) and Scientific Approach in Inequality Absolute Value, Fraction, and Irrational material which covered Lesson Plan, Students Book, and Students Worksheet. The subjects of the research were the students of class X at SMAN 2 Polewali Mandar District with the total of 35 students. The Development procedure of the research employed Thiagarajan Model (4-D) which covered four stages, namely defining, design, development, and dissemination. The result of limited test showed that (1) the average score obtained by the students in learning result test is 75.42 from ideal score by 100 with deviation standard 8.69 where 29 from 35 students or 82.85% met individual completeness which shows that classical completeness had been reached; (2) by using Mathematics learning devices with Cooperative Model with the Combination Of Experiences, Language, Pictorial, Symbol, Application (ELPSA) and Scientific Approach, the students are more active in the learning process; (3) in general, the students gave good responses on the learning devices used; and (4) the level of teacher’ abilities in managing learning process of Cooperative Model with the Combination Of Experiences, Language, Pictorial, Symbol, Application (ELPSA) and Scientific Approach is in good category, meaning that the teachers’ performances can be maintained. Based on the results of the research, it can concluded that Mathematics learning devices with Cooperative Model with the Combination Of Experiences, Language, Pictorial, Symbol, Application (ELPSA) and Scientific Approach developed has met the requirement of valid, effective, and practical criteria.